Refugees: Challenges to protection - Goodwin-Gill, G (2001)
By the end of the year 2000, the Office of the United Nations High Commissioner for Refugees will have been in existence for 50 years-which is probably some sort of record for an organization originally set up with just a three-year mandate. There were many reasons for so limiting the successor agency to the International Refugee Organization, but it is doubtful whether anyone seriously thought that refugee problems would be resolved so quickly, or indeed that UNHCR would develop into the highly operational, visible and extensively funded entity that we see today. Fifty years of experience nevertheless suggests that it is high time for an audit, for an evaluation of strengths, weaknesses and achievements, and a little strategic thinking about the future.